Concise Review: Application of In Vitro Transcribed Messenger RNA for Cellular Engineering and Reprogramming: Progress and Challenges. (20th June 2016) - Steinle, Heidrun; Behring, Andreas; Schlensak, Christian; Wendel, Hans Peter; Avci-Adali, Meltem
Abstract : Several diseases are caused by missing or defective synthesis of proteins due to genetic or acquired disorders. In recent years, in vitro transcribed (IVT) messenger RNA (mRNA)-based therapy for de novo protein expression in cells has increased in importance. Thereby, desired proteins can be produced in cells by exogenous delivery of IVT mRNA, which does not integrate into the host genome and results in transient production of target proteins. Due to the lack of genomic integration, the risk of mutation and tumor development is minimized. Different approaches using IVT mRNA have been applied to alter the expression profiles of cells by the production of proteins. IVT mRNAs encoding transcription factors have led to the highly efficient induction of pluripotency in somatic cells and generated induced pluripotent stem cells that are free of viral vector components. Furthermore, specific IVT mRNA cocktails containing more than one specific IVT mRNA can be used to directly induce the differentiation into a desired cell type. In theory, every desired mRNA can be produced in vitro and used to enable extrinsic biosynthesis of target proteins in each cell type. Cells can be engineered by IVT mRNA to express antigens on dendritic cells for vaccination and tumor treatment, surface receptors on stem cells for increased homing to distinct areas, and to produce industrial grade human growth factors. In this review, we focus on the progress and challenges in mRNA-based cell engineering approaches.